Hey there! Sign in to join this conversationNew here? Join for free
    • Thread Starter
    Offline

    2
    ReputationRep:
    http://www.examsolutions.net/a-level...y/paper.php#Q6

    how do i draw a graph of

    ln(1-x)?

    i can drawn ln(1+x)\ or\ ln(x-1)\ or\ ln(2x)\ or\ ln(x^2)

    but they never taught me how to draw a graph of ln something minus x how do i do it?
    Offline

    15
    ReputationRep:
    It will just be a few simple transformations (reflections, translations) so the graph will still look similar.
    You may need to just re write it using latex because I can't really understand what you have put.
    Offline

    2
    ReputationRep:
    (Original post by timebent)
    http://www.examsolutions.net/a-level...y/paper.php#Q6

    how do i draw a graph of

    ln1-x?

    i can drawn ln1+x\ or\ lnx-1\ or\ ln2x\ or\ lnx^2

    but they never taught me how to draw a graph of ln something minus x how do i do it?
    You realise ln1 is just 0 so in fact you're just drawing -x which is just a straight line through the origin with a negative gradient
    • Thread Starter
    Offline

    2
    ReputationRep:
    (Original post by B_9710)
    It will just be a few simple transformations (reflections, translations) so the graph will still look similar.
    You may need to just re write it using latex because I can't really understand what you have put.
    you want some brackets? i guess i should probably put them in, check back again after you get the notification
    (Original post by target21859)
    You realise ln1 is just 0 so in fact you're just drawing -x which is just a straight line through the origin with a negative gradient
    yes but surely this is the transformation of
    and thus i'd just move the graph right 1 unit?

    but yea i want to reflect it in the y-axis if it's -x
    Offline

    22
    ReputationRep:
    (Original post by target21859)
    You realise ln1 is just 0 so in fact you're just drawing -x which is just a straight line through the origin with a negative gradient
    He (obviously) means \ln (1-x).

    @OP. Denote f(x) = \ln x then g(x) = f(-x) = \ln (-x) is a reflection in the y-axis of f(x). Draw this.

    Now h(x) = g(x+1) = \ln(-x +1) = \ln(1-x) which is a translation to the left by one unit of g(x). Can you now draw this?
    Offline

    2
    ReputationRep:
    (Original post by timebent)
    you want some brackets? i guess i should probably put them in, check back again after you get the notification

    yes but surely this is the transformation of and thus i'd just move the graph right 1 unit?

    but yea i want to reflect it in the y-axis if it's -x
    This is just f(-x) as the a part is 0 because ln1=0
    Edit: just saw Zacken's post. Didn't realise there were meant to be brackets so ignore my posts lol.
    • Thread Starter
    Offline

    2
    ReputationRep:
    (Original post by Zacken)
    He (obviously) means \ln (1-x).

    @OP. Denote f(x) = \ln x then g(x) = f(-x) = \ln (-x) is a reflection in the y-axis of f(x). Draw this.

    Now h(x) = g(x+1) = \ln(-x +1) = \ln(1-x) which is a translation to the left by one unit of g(x). Can you now draw this?
    so 1 unit to the left of the graph y=\ln x reflected in the y-axis?

    (Original post by target21859)
    This is just f(-x) as the a part is 0 because ln1=0
    Edit: just saw Zacken's post. Didn't realise there were meant to be brackets.
    sorry about that
    Offline

    22
    ReputationRep:
    (Original post by timebent)
    so 1 unit to the left of the graph y=\ln x reflected in the y-axis?

    Yes.
    • Thread Starter
    Offline

    2
    ReputationRep:
    (Original post by Zacken)
    Yes.
    awesome

    so what about the flipside

    y=2-\dfrac{1}{2} e^x

    what about one of these?
    Offline

    22
    ReputationRep:
    (Original post by timebent)
    awesome

    so what about the flipside

    y=2-\dfrac{1}{2} e^x

    what about one of these?
    You work through it for yourself systematically first before opening the spoiler below, it's all very procedural.
    Spoiler:
    Show
    Call f(x) = e^x. Draw it.

    Now stretch this by a factor of \frac{1}{2} in the direction parallel to the y-axis (i.e: flatten it vertically by half). This gives you g(x) = \frac{1}{2}f(x) = \frac{1}{2}e^x.

    Now flip this in the x-axis, this is h(x) = -g(x) = -\frac{1}{2}e^x. Draw it.

    Now translate this upwards by 2 units. This gives you m(x) = 2 + h(x) = 2 + -\frac{1}{2}e^x = 2 - \frac{1}{2}e^x
    • Thread Starter
    Offline

    2
    ReputationRep:
    (Original post by Zacken)
    You work through it for yourself systematically first before opening the spoiler below, it's all very procedural.
    Spoiler:
    Show
    Call f(x) = e^x. Draw it.

    Now stretch this by a factor of \frac{1}{2} in the direction parallel to the y-axis (i.e: flatten it vertically by half). This gives you g(x) = \frac{1}{2}f(x) = \frac{1}{2}e^x.

    Now flip this in the x-axis, this is h(x) = -g(x) = -\frac{1}{2}e^x. Draw it.

    Now translate this upwards by 2 units. This gives you m(x) = 2 + h(x) = 2 + -\frac{1}{2}e^x = 2 - \frac{1}{2}e^x
    i drew the graph like this.
    y=e^x\ y=\frac{1}{2}e^x
    y=-0.5e^x y=2-0.5e^x


    i wasn't sure whether it went above the x-axis or not :/
    Attached Images
     
    Offline

    22
    ReputationRep:
    (Original post by timebent)
    i drew the graph like this.
    y=e^x\ y=\frac{1}{2}e^x

y=-\frac{1}{2}e^x\ y=2-\frac{1}{2}e^x

    i wasn't sure whether it went above the x-axis or not :/
    1. Your attempts to use LaTeX aren't helping, could you please stick to/at least provide ascii typed mathematical expressions of the form y = e^x, y = (1/2) e^x, etc... so that we may understand what you are saying.

    2. You should know basic properties of \exp. It has an asymptote at the x-axis, so y=0. The first transformation, halving the function "changes" the asymptote to y = \frac{0}{2} = 0. The second transformation, reflecting the curve "changes the asymptote to y = -\frac{0}{2} = 0. The third transformation shifts the asymptote 2 units upwards, so changes it to y = -\frac{0}{2} + 2 = 2. So your graph is correct, indeed it is asymptotic to the line y = 2 as x \to -\infty and then diverges off to negative infinity as x \to \infty. Furthermore, it has a y-intercept of (0, 1) and an x-intercept at (\ln 2, 0).
    • Thread Starter
    Offline

    2
    ReputationRep:
    (Original post by Zacken)
    1. Your attempts to use LaTeX aren't helping, could you please stick to/at least provide ascii typed mathematical expressions of the form y = e^x, y = (1/2) e^x, etc... so that we may understand what you are saying.

    2. You should know basic properties of \exp. It has an asymptote at the x-axis, so y=0. The first transformation, halving the function "changes" the asymptote to y = \frac{0}{2} = 0. The second transformation, reflecting the curve "changes the asymptote to y = -\frac{0}{2} = 0. The third transformation shifts the asymptote 2 units upwards, so changes it to y = -\frac{0}{2} + 2 = 2. So your graph is correct, indeed it is asymptotic to the line y = 2 as x \to -\infty and then diverges off to negative infinity as x \to \infty. Furthermore, it has a y-intercept of (0, 1) and an x-intercept at (\ln 2, 0).
    So y-intercept means x=0

    so if i stick x=0 into y=2-\frac{1}{2} e^x e^x becomes 1
    1x0.5=0.5
    so 2-0.5=1.5 which isn't 1 or did i go wrong somewhere?

    and it touches the x axis at y=0
    so when y=0
    0=2-\frac{1}{2} e^x

    2=\frac{1}{2} e^x

    4=e^x

    ln4=x

    where did it all go wrong?
    Offline

    22
    ReputationRep:
    (Original post by timebent)
    So y-intercept means x=0

    so if i stick x=0 into y=2-\frac{1}{2} e^x e^x becomes 1
    1x0.5=0.5
    so 2-0.5=1.5 which isn't 1 or did i go wrong somewhere?

    and it touches the x axis at y=0
    so when y=0
    0=2-\frac{1}{2} e^x

    2=\frac{1}{2} e^x

    4=e^x

    ln4=x

    where did it all go wrong?
    Yeah, that's all fine. I thought the function was 2 - e^x whilst writing my reply up, hence the discrepancy.
    • Thread Starter
    Offline

    2
    ReputationRep:
    (Original post by Zacken)
    Yeah, that's all fine. I thought the function was 2 - e^x whilst writing my reply up, hence the discrepancy.
    ah ok It's all good
 
 
 
  • See more of what you like on The Student Room

    You can personalise what you see on TSR. Tell us a little about yourself to get started.

  • Brussels sprouts
    Useful resources

    Make your revision easier

    Maths

    Maths Forum posting guidelines

    Not sure where to post? Read the updated guidelines here

    Equations

    How to use LaTex

    Writing equations the easy way

    Student revising

    Study habits of A* students

    Top tips from students who have already aced their exams

    Study Planner

    Create your own Study Planner

    Never miss a deadline again

    Polling station sign

    Thinking about a maths degree?

    Chat with other maths applicants

    Can you help? Study help unanswered threads

    Groups associated with this forum:

    View associated groups
  • See more of what you like on The Student Room

    You can personalise what you see on TSR. Tell us a little about yourself to get started.

  • The Student Room, Get Revising and Marked by Teachers are trading names of The Student Room Group Ltd.

    Register Number: 04666380 (England and Wales), VAT No. 806 8067 22 Registered Office: International House, Queens Road, Brighton, BN1 3XE

    Quick reply
    Reputation gems: You get these gems as you gain rep from other members for making good contributions and giving helpful advice.